Electrically insulated conductor and method for electrically insulating conductor
By adopting a double-layer insulation solution on the electric motor wire, combined with an enameled coating and a polyimide electrical insulation belt, the problem of partial discharge at 800V voltage is solved, and the uniformity of the conductor insulation and anti-discharge capability are achieved.
Patent Information
- Application Number
- CN202411530253.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-10-25
- Filing Date
- 2024-10-30
- Publication Date
- 2025-05-02
AI Technical Summary
The wire insulation materials in existing electric motors are prone to partial discharge (PD) at 800V voltage, resulting in insulation failure and short-circuit of the electric motor. The traditional enameled coating has defects such as uniformity problems and solvent residues during the production process.
A double-layer insulation scheme is adopted, first apply an enameled coating along the electrical conductor, then wrap the electrical insulating tape containing polyimide around the enameled electrical conductor, and ensure good adhesion of the insulating tape to the enameled packet is ensured by heating sealing.
It realizes the local discharge resistance of the wire insulating material, and is suitable for electric motors above 800V. This double-layer solution can ensure the uniformity of the insulation thickness during the production process, reducing the need for treatment solvents.
Smart Images

Figure BDA0005110301480000181 
Figure BDA0005110301480000191
Abstract
Description
Technical Field
[0001] The present disclosure relates generally to electrically insulated conductors and methods for electrically insulating conductors such that they are resistant to partial discharge (PD) and are thereby suitable for PD resistant designs (eg, electric motors operating above 800V, etc.). Background Art
[0002] This section provides background information related to the present disclosure which is not necessarily prior art.
[0003] Electric vehicles are commonly used today, and their use is expected to increase significantly over time. Electric motors used in electric vehicles may be driven by a pulse width modulation (PWM) inverter. Summary of the invention
[0004] The present disclosure provides a method for electrically insulating a conductor to make the resulting electrically insulated conductor resistant to partial discharge (PD), the method comprising: applying an enameled coating along the electrical conductor; wrapping an electrically insulating tape around the enameled electrical conductor, the electrically insulating tape comprising a polyimide, an additional polymer adhered to the polyimide, and an electrically insulating anti-corona filler in an amount sufficient to resist PD; and heat-sealing the enameled electrical conductor wrapped with the tape to help ensure good adhesion of the electrically insulating tape to the enameled coating; thereby, the enameled electrical conductor wrapped with the tape is resistant to PD.
[0005] The present disclosure also provides an electrically insulated conductor, comprising: a conductive core; an enameled coating along the conductive core; and an electrically insulating tape wound around the enameled conductive core, the electrically insulating tape comprising polyimide, an additional polymer adhered to the polyimide, and an electrically insulating anti-corona filler in an amount sufficient to resist partial discharge (PD); thereby, the enameled conductive core wrapped with the tape is resistant to PD. DETAILED DESCRIPTION
[0006] Hairpin winding technology is becoming more common in the design of electric motors (e-motors) for electric vehicles, especially for traction motor applications that require high power density. Another common design change in e-motors is the increase in system voltage from the current 400V standard to 800V. The increase to 800V puts more stress on the wire insulation around the copper hairpin bars in the e-motors. And the failure of the wire insulation used to insulate the copper conductors to prevent shorts to ground in the e-motors will render the entire e-motors useless, which cannot be repaired.
[0007] A particular stress to which the wire insulation may be subjected in an 800V electric motor is so-called "partial discharge" ("PD"). Partial discharge is a phenomenon in which, under certain conditions, the wire insulation continues to degrade due to the action of an applied electric field until the insulation eventually fails and the electric motor shorts out. Partial discharge is not a problem with the insulation materials typically used in 400V electric motors, and can be avoided in 800V electric motors as part of so-called "PD-free" motor designs. In a PD-free design, the thickness of the wire insulation is increased above a certain thickness threshold that is derived from an empirical formula known in the industry, and the occurrence of the PD phenomenon is avoided. A disadvantage of increasing the thickness of the wire insulation is that it reduces the amount of copper that can be placed into the electric motor (commonly referred to as the copper fill factor), which increases the resistance of the copper wire inside the electric motor, thereby reducing the performance of the electric motor. Therefore, the safer PD-free design of electric motors directly leads to reduced motor performance.
[0008] The competing design approach for wire insulation in 800V electric motors is the so-called “PD-resistant” design. In a PD-resistant design, the wire insulation material is kept thinner than is necessary to avoid partial discharge phenomena inside the electric motor, which allows for a higher copper filling factor. In order to cope with the partial discharge phenomena that now occur inside electric motors, the insulation material is made resistant to partial discharge, which is why such designs are often referred to as “PD-resistant” designs. Resistance of the wire insulation material to PD is usually achieved by filling portions of the wire insulation material (usually composed of an organic polymer) with inorganic fillers.
[0009] As further recognized herein, the industry standard for wire insulation in 400V electric motors is currently a varnish / enamel organic polymer that is coated on rectangular copper wires (less commonly round copper wires or aluminum as the conductor material) before the rectangular copper wires are inserted into the electric motor. Increasing the system voltage of electric vehicles from 400V to 800V requires the application of thicker insulation materials around the individual wires within the electric motor to keep up with the increased electrical insulation requirements and remain in a PD-free design state. However, the use of thicker enamel coatings (i.e., "Grade 3", enamel thickness of 100μm or more) has limitations in its production: first, as the thickness increases, it is difficult to achieve uniformity in the thickness of the enamel coating around the wire with enameled rectangular copper wire (especially at the corners or edges of the wire where the wire presents a small corner radius). Second, residual solvent content is a common problem with thick grade enamels. Solvents used in the enameling process (e.g., N,N-dimethylacetamide (DMAc) or N-methylpyrrolidone NMP) have come under increasing scrutiny in parts of the world such as Europe, where regulatory agencies in the European Union (EU) have strongly recommended elimination of these solvents. Additionally, mechanical stresses applied to the enameling coating during the formation of the enameled wire (to create hairpins that are then inserted into the electric motor) can cause pinhole or crack problems in the enameling, leading to electrical failures. Furthermore, temperatures during the hairpin welding process (which connects the individual hairpins in the electric motor to the adjacent circuit) can locally affect the wire insulation, creating weak points in the enameling. For example, heat exposure during the welding process will make the enameling brittle and susceptible to electrical failures.
[0010] An alternative to achieving a higher insulation thickness around the copper conductor is to use an extrusion process (instead of a coating process using an enamel). In this scheme, a polymer (typically a polyaryletherketone (PAEK) having a glass transition temperature of about 140°C to 160°C) is extruded onto the conductor, which allows a continuous insulation layer of more than 200 μm thickness to be formed on each side, which is sufficient to remain in a PD-free design state. In order to achieve better adhesion of PAEK to the copper conductor, a thin primer layer (such as an enamel coating) can first be applied to the conductor and then the PAEK polymer can be extruded thereon (see, for example, U.S. Pat. No. 9,224,523 and U.S. Pat. No. 9,536,636, which are incorporated herein by reference). Common enamel types, such as polyimide, polyamide-imide or polyamide-imide / polyester-imide. Can be used as a primer. A disadvantage of using PAEK based insulation is that its thermal transition point (more specifically: glass transition point) is usually lower than the operating temperature of the electric motor (typically 180°C to 200°C), which may create potential issues regarding the long term reliability of such wire insulation materials.
[0011] A third solution is to wrap the copper conductor with tape. This results in insulation that has edges on the surface rather than a smooth surface. The tape can be made from a variety of materials, but typically polyimide-based tapes are used for applications in harsh environments such as electric motors. The polyimide tape may contain inorganic fillers to make it PD-resistant and may contain one or more fluoropolymer-based layers on the surface that act as an adhesive to provide adhesion to the copper conductor. The disadvantage of using tape insulation is that delamination, wear and scratching of the tape insulation can occur when the wire is bent to create a hairpin, completely piercing the tape insulation and creating an electrical failure.
[0012] After recognizing the above, exemplary embodiments have been developed and / or disclosed herein in which wires (broadly, electrical conductors) are insulated based on a partial discharge (PD) resistant design approach, such that the insulated wires can be used in electric motors above 800 V. The exemplary embodiments disclosed herein use a dual-layer approach for wire insulation by incorporating an enamel coating underneath a polyimide-containing tape wrap, whereby the electrically insulated conductors are PD resistant and can be used in applications above 800 V.
[0013] In an exemplary embodiment, an enamel coating (e.g., up to 90 μm thick per side on average, but more preferably in the range of 50 μm to 70 μm average thickness, etc.) is applied to a copper conductor (broadly, an electrical conductor) and cured. Then, a tape containing polyimide is wrapped around the enameled copper conductor with an overlap value of the tape (e.g., in the range of 15% to 70%, etc.), and heat sealed to ensure good adhesion of the tape to the enamel. The polyimide-containing tape includes an electrically insulating anti-corona composite filler (e.g., alumina, etc.) in a sufficient amount (e.g., 17 weight percent (wt%), etc.) for anti-PD in the polyimide polymer.
[0014] The advantage of this double layer approach is that the resulting wire insulation material has an overall average thickness of less than 170 μm per side, which results in a theoretically higher copper filling factor compared to PAEK-based extrusion materials if the same copper conductor size is used. In addition, the resulting wire insulation material is able to withstand partial discharge (PD) phenomena, making it suitable for PD-resistant designs such as electric motors above 800V. Compared to using enamel only on the copper wire, this double layer approach enables a uniform insulation thickness around the copper wire and requires less processing solvents during the production of the insulated copper wire. Compared to a tape-only insulation system, this double layer approach includes an enamel that still exists under the tape winding and still provides electrical insulation in the event of delamination or scratching of the applied tape.
[0015] Enamel coating process
[0016] A description of the enamel coating process used in an exemplary embodiment will now be provided. In an exemplary embodiment, the electrical conductors that can be used for the enamel coating process are primarily composed of copper (preferably classified as copper of CDA 10100, 10200 and 110000) or aluminum. Other conductors include alloys of copper with other metals, stainless steel and graphite. The electrical conductor preferably has a rectangular shape with a defined corner radius of less than 1 millimeter (mm) and a size of about 1 to 6 millimeters by 1.5 to 20 millimeters, and the performance described in ASTM B250, ASTM B48, ANSI / NEMAMW 1000 and / or IEC 60317. However, electrical conductors with other shapes (e.g., round, square, stranded, braided wire, hollow, etc.) may also be used in exemplary embodiments. Additional dimensions of electrical conductors with a rectangular shape used in busbar applications above 800V include 1 to 20 mm by 20 to 200 mm, with a corner radius of 0.1 to 0.3 mm.
[0017] In an exemplary embodiment, the enamel is applied to a bare rectangular copper conductor by a method disclosed in, for example, U.S. Patent 2345390, U.S. Patent 9543058 and / or U.S. Patent 10020092. As known in the art, the performance of the cured enamel can be affected by carefully selecting processing parameters such as line speed, curing temperature, line tension, absolute humidity and temperature of the surrounding atmosphere, the thickness of the wet coating applied, the form and shape of the coating die, the residual solvent content and the viscosity of the coating solution applied. For example, the degree of cure, adhesion, uniformity and concentricity of the coating thickness, wear resistance and scratch resistance, resistance to organic solvents and moisture resistance, the hardness of the cured enamel, etc. are directly affected by the careful selection of these processing parameters. In an exemplary embodiment, the average thickness of each side of the enamel is less than 90 microns. In another exemplary embodiment, the preferred average thickness range of each side of the enamel is 30 to 80 microns.
[0018] In an exemplary embodiment, the chemical composition of the enamel is generally described as a polyamide-imide (e.g., described in DOI 10.1002 / mame.200700365 or Applied Plastics Engineering Handbook (2011), Part 1, Chapter 2 or Plastics in Medical Devices (2010), Chapter 8), a polyimide (formally derived from monomers disclosed in the subsection entitled "Production of Polyimide Films" below), a polyester-imide (e.g., described in DOI 10.1002 / mame.200700363), or a combination thereof. For example, the enamel coating can be a single chemical composition. Alternatively, for example, the enamel coating can include multiple layers of different compositions coated on each other. In this case, the thickness of each layer is not limited by the presence of other layers. A preferred enamel composition is a polyamide-imide, more specifically, a polymer formally derived from a diamine (such as 4,4'-methylenedianiline) and an anhydride (such as trimellitic anhydride). Other diamines derived formally from monomers as disclosed below in the section entitled "Production of Polyimide Films" may also be applied in the polyamide-imide enamel composition alone or as part of a mixture of two or more diamines. Additional layers may be present to improve adhesion or to improve scratch and abrasion resistance or other properties relevant to the application. The surface of the wire bearing the enamel coating is preferably free of any lubricants or other layers intended to reduce the surface energy of the enamel coating.
[0019] In an exemplary embodiment, the surface of the enamel coating can be treated in a manner to increase adhesion to a layer (e.g., tape) subsequently placed on the enamel surface. Suitable means for improving adhesion include the methods disclosed in the subsequent sections below, and may include plasma or corona treatments, but are not limited to these.
[0020] An electrical conductor that is completely covered in an enamel can have certain desirable properties. Desirable properties include (a) a visible appearance of the enamel that is free of defects such as blisters or bubbles, (b) a thermal rating of 200°C or higher when the enamel is applied to copper, (c) a residual solvent content of 5 wt% or less, (d) a breakdown voltage value of at least 2 kV or higher that is retained to at least 50% of its initial value after the conductor has been elongated by at least 5%, bent, chemically exposed, or thermally exposed, (e) no visible cracking when rotated about a mandrel having a diameter of twice the conductor width along an edge or bent 180° along a plane, (f) a dielectric strength of at least 200°C or higher when exposed to a temperature of at least 200°C or higher. No visible cracking for at least 30 minutes, or when additionally first bent along a plane or along an edge, or when additionally first elongated to at least 10%, (g) an elongation at break of at least 30%, (h) after elongation of at least 20% or additionally when first heat aged at at least 150°C for at least 30 minutes, the loss of adhesion of the enamel is less than 1 times the conductor width, (i) a certain static friction coefficient, (j) a certain partial discharge inception voltage at a threshold of 20 pico-coulombs above 700V under ambient conditions, and (k) a certain abrasion / scratch resistance. Testing of these properties can be carried out according to standard procedures known in the industry such as IEC 60851, ASTM or ANSI / NEMA MW 1000.
[0021] Production of polyimide film
[0022] In an exemplary embodiment, the belt is composed of a polyimide layer of nominal thickness (e.g., 0.75 mils, etc.) and a fluoropolymer layer of nominal thickness (e.g., 0.5 mils, etc.). The chemical composition of the polyimide layer is preferably a copolymer of 4,4'-diphenyl ether and pyromellitic anhydride, and contains a predetermined weight % (e.g., 17 weight %, etc.) of uniformly dispersed inorganic fillers (e.g., alumina, etc.). The inorganic filler is surface treated with silane, and a dispersant is used as a processing aid to uniformly disperse the filler during the film production step. In an exemplary embodiment, the particle size distribution of the alumina filler is d99 measured by a LA-960 Horiba particle size analyzer of less than 0.5 μm. The chemical composition of the fluoropolymer layer is preferably a fluorinated ethylene propylene copolymer (FEP).
[0023] A more detailed description of polyimide compositions, fluoropolymer compositions, and film production according to exemplary embodiments is provided below.
[0024] Diamine monomers suitable for producing polyimide layers
[0025] In an exemplary embodiment, any number of suitable diamines may be used as monomers to form the polymer backbone. The aromatic diamine may include fluorinated aromatic diamines such as 2,2'-bis(trifluoromethyl)benzidine (TFMB), 2,2'-bis-(4-aminophenyl)hexafluoropropane, 4,4'-diamino-2,2'-trifluoromethyl diphenyl ether, 3,3'-diamino-5,5'-trifluoromethyl diphenyl ether, 9,9'-bis(4-aminophenyl)fluorene, 4,4'-trifluoromethyl-2,2'-diaminobiphenyl, 4,4'-oxy-bis[2-trifluoromethyl)aniline] (1,2,4-OBABTF), 4,4'-oxy-bis[3-trifluoromethyl)aniline], 4,4'-thiobis[(2-trifluoromethyl)aniline], 4,4'-thiobis[(3-trifluoromethyl)aniline], 4,4'-sulfoxide-bis[(2-trifluoromethyl)aniline, 4,4'-sulfoxide-bis[(3-trifluoromethyl)aniline], 4,4'-keto-bis[(2-trifluoromethyl)aniline], 1,1-bis[4'-(4"-amino- 2"-trifluoromethylphenoxy)phenyl]cyclopentane, 1,1-bis[4'-(4"-amino-2"-trifluoromethylphenoxy)phenyl]cyclohexane, 2-trifluoromethyl-4,4'-diaminodiphenyl ether, 1,4-(2'-trifluoromethyl-4',4"-diaminodiphenyloxy)benzene, 1,4-bis(4'-aminophenoxy)-2-[(3',5'-ditrifluoromethyl)phenyl]benzene(6F-amine), 1,4-bis[2'-cyano-3'("4 -aminophenoxy)phenoxy]-2-[(3',5'-ditrifluoromethyl)phenyl]benzene (6FC-diamine), 3,5-diamino-4-methyl-2',3',5',6'-tetrafluoro-4'-trifluoromethyl diphenyl ether, 2,2-bis[4(4-aminophenoxy)phenyl]phthalein-3',5'-bis(trifluoromethyl)aniline (6FADAP), and 3,3',5,5'-tetrafluoro-4,4'-diaminodiphenylmethane (TFDAM).
[0026] Other useful aromatic diamines may include 4,4'-diaminobiphenyl, 4,4"-diaminoterphenyl, 4,4'-diaminobenzanilide (DABA), 4,4'-diaminophenylbenzoate, 4,4'-diaminobenzophenone, 4,4'-diaminodiphenylmethane (MDA), 4,4'-diaminodiphenyl sulfide, 4,4'-diaminodiphenyl sulfone, 3,3'-diaminodiphenyl sulfone, bis[4-(4-aminophenoxy)phenyl]sulfone (BAPS), 4,4'-bis(4-aminophenoxy)biphenyl (BAPB), 4,4'-diaminodiphenyl ether ( In some embodiments, the diamine is 2-(4-aminophenyl)-1-nitropropane, ...
[0027] Other useful aromatic diamines may include 1,2-bis(4-aminophenoxy)benzene, 1,3-bis(4-aminophenoxy)benzene (RODA), 1,2-bis(3-aminophenoxy)benzene, 1,3-bis(3-aminophenoxy)benzene, 1-(4-aminophenoxy)-3-(3-aminophenoxy)benzene, 1,4-bis-(4-aminophenoxy)benzene, 1,4-bis(3-aminophenoxy)benzene, 1-(4-aminophenoxy)-4-(3-aminophenoxy)benzene, 2,2-bis(4-[4-aminophenoxy]phenyl)propane (BAPP), and 2,2'-bis(4-phenoxyaniline)isopropylmethylene.
[0028] Other useful aromatic diamines may include p-phenylenediamine (PPD), m-phenylenediamine (MPD), 2,5-dimethyl-1,4-diaminobenzene, 2,5-dimethyl-1,4-phenylenediamine (DPX), 1,4-naphthalenediamine, 1,5-naphthalenediamine, 1,5-diaminonaphthalene, m-phenylenediamine, and p-phenylenediamine.
[0029] In an exemplary embodiment, other useful diamines for forming polyimides may include aliphatic diamines such as 1,2-diaminoethane, 1,6-diaminohexane (HMD), 1,4-diaminobutane, 1,5-diaminopentane, 1,7-diaminoheptane, 1,8-diaminooctane, 1,9-diaminononane, 1,10-diaminodecane (DMD), 1,11-diaminoundecane, 1,12-diaminododecane (DDD), 1,16-hexadecamethylenediamine, 1,3-bis(3-aminopropyl)-tetramethyldisiloxane, trans-1,4-diaminocyclohexane (CHDA), isophoronediamine (IPDA), bicyclo[2.2.2]octane-1,4-diamine, and combinations thereof. Other aliphatic diamines suitable for use in the practice of the present invention include aliphatic diamines having six to twelve carbon atoms or a combination of long and short chain diamines, as long as the ductility and flexibility of the polymer are maintained. Long chain aliphatic diamines can increase flexibility.
[0030] Other useful additional diamines for forming polyimides may include alicyclic diamines (which may be fully or partially saturated), such as cyclobutane diamines (e.g., cis- and trans-1,3-diaminocyclobutane, 6-amino-3-azaspiro[3.3]heptane, and 3,6-diaminospiro[3.3]heptane), bicyclo[2.2.1]heptane-1,4-diamine, isophorone diamine, and bicyclo[2.2.2]octane-1,4-diamine. Other alicyclic diamines may include cis-1,4-cyclohexane diamine, trans-1,4-cyclohexane diamine, 1,4-bis(aminomethyl)cyclohexane, 4,4'-methylenebis(cyclohexylamine), 4,4'-methylenebis(2-methylcyclohexylamine), bis(aminomethyl)norbornane.
[0031] Dianhydride monomers suitable for the production of polyimide layers
[0032] In exemplary embodiments, any number of suitable dianhydrides can be used as monomers to form a polymer backbone. The dianhydride can be used in the form of a tetraacid form (or a monoester, diester, triester or tetraester of a tetraacid) or a diester halide (chloride). However, in some exemplary embodiments, the dianhydride form may be preferred because it is generally more reactive than an acid or ester.
[0033] Examples of suitable aromatic dianhydrides include 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA), 2-(3',4'-dicarboxyphenyl)-5,6-dicarboxybenzimidazole dianhydride, 2-(3',4'-dicarboxyphenyl)-5,6-dicarboxybenzoxazole dianhydride, 2-(3',4'-dicarboxyphenyl)-5,6-dicarboxybenzothiazole dianhydride, 2,2',3,3'-benzophenonetetracarboxylic dianhydride, 2 ,3,3',4'-benzophenonetetracarboxylic dianhydride, 3,3',4,4'-benzophenonetetracarboxylic dianhydride (BTDA), 2,2',3,3'-biphenyltetracarboxylic dianhydride, 2,3,3',4'-biphenyltetracarboxylic dianhydride, 4,4'-thiodiphenyl anhydride, bis(3,4-dicarboxyphenyl)sulfone dianhydride, bis(3,4-dicarboxyphenyl)sulfoxide dianhydride (DSDA), bis(3,4-dicarboxyphenyloxadiazole-1 ,3,4)-terephthalic anhydride, bis(3,4-dicarboxyphenyl)-2,5-oxadiazole-1,3,4-dianhydride, bis(3',4'-dicarboxydiphenyl ether)-2,5-oxadiazole-1,3,4-dianhydride, 4,4'-oxydiphenyl anhydride (ODPA), bis(3,4-dicarboxyphenyl) sulfide dianhydride, bisphenol A dianhydride (BPADA), bisphenol S dianhydride, bis-1,3-isobenzofurandione, 1,4-bis( 4,4'-oxydiphthalic anhydride)benzene, bis(3,4-dicarboxyphenyl)methane dianhydride, perylene-3,4,9,10-tetracarboxylic dianhydride, 1,3-bis-(4,4'-oxydiphthalic anhydride)benzene, 2,2-bis(3,4-dicarboxyphenyl)propane dianhydride, 4,4'-(hexafluoroisopropylmethylene)diphthalic anhydride (6FDA) and 9,9-bis(trifluoromethyl)-2,3,6,7-xanthenetetracarboxylic anhydride.
[0034] In an exemplary embodiment, the additional dianhydride used to form the polyimide may include 1,2,5,6-naphthalenetetracarboxylic dianhydride, 1,4,5,8-naphthalenetetracarboxylic dianhydride, 2,3,6,7-naphthalenetetracarboxylic dianhydride, bicyclo-[2,2,2]-octene-(7)-2,3,5,6-tetracarboxylic dianhydride, cyclopentadienyltetracarboxylic dianhydride, ethylenetetracarboxylic dianhydride, pyromellitic dianhydride (PMDA), Tetrahydrofurantetracarboxylic dianhydride, 2,6-dichloronaphthalene-1,4,5,8-tetracarboxylic dianhydride, 2,7-dichloronaphthalene-1,4,5,8-tetracarboxylic dianhydride, 2,3,6,7-tetrachloronaphthalene-1,4,5,8-tetracarboxylic dianhydride, phenanthrene-1,8,9,10-tetracarboxylic dianhydride, pyrazine-2,3,5,6-tetracarboxylic dianhydride, benzene-1,2,3,4-tetracarboxylic dianhydride, thiophene-2,3,4,5-tetracarboxylic dianhydride.
[0035] In exemplary embodiments, the additional dianhydride used to form the polyimide may include alicyclic dianhydrides such as cyclobutane-1,2,3,4-tetracarboxylic dianhydride (CBDA), 1,2,4,5-cyclohexanetetracarboxylic dianhydride, 1,2,3,4-cyclohexanetetracarboxylic dianhydride, 1,2,3,4-tetramethyl-1,2,3,4-cyclobutanetetracarboxylic dianhydride, 1,2,3,4-cyclopentanetetracarboxylic dianhydride (CPDA), hexahydro-4,8-ethyl-1H,3H-benzo[1,2-c:4,5-c']difuran-1,3,5,7-tetraone (BODA), 3-(carboxymethyl)-1,2,4-cyclopentanetricarboxylic acid 1,4:2,3-dianhydride (TCA), and meso-butane-1,2,3,4-tetracarboxylic dianhydride.
[0036] In an exemplary embodiment, the polyimide is derived from 50 mol% of pyromellitic dianhydride (PMDA) and 50 mol% of 4,4'-diaminodiphenyl ether (ODA). In an exemplary embodiment, the polyimide may have a weight average molecular weight (Mw) of 100,000 Daltons or more, 150,000 Daltons or more, 200,000 Daltons or more, or 250,000 Daltons or more.
[0037] Imidization catalyst
[0038] In an exemplary embodiment, an imidization catalyst (sometimes referred to as an "imidization accelerator") can be used as a conversion chemical that can help reduce the imidization temperature of the polyimide and shorten the imidization time. The polyamic acid casting solution of the present invention includes a polyamic acid solution and a certain amount of conversion chemicals. Conversion chemicals found to be useful in the present invention include, but are not limited to (i) one or more dehydrating agents and / or promoters, such as aliphatic anhydrides (acetic anhydride, trifluoroacetic anhydride, propionic anhydride, monochloroacetic anhydride, bromoadipic anhydride, etc.) and aromatic anhydrides; and (ii) one or more imidization catalysts, such as aliphatic tertiary amines (triethylamine, etc.), aromatic tertiary amines (dimethylaniline, N,N-dimethylbenzylamine, etc.) and heterocyclic tertiary amines (pyridine, α-, β-, γ-pyridine, 3,5-lutidine, 3,4-lutidine, isoquinoline, etc.) and guanidine (e.g., tetramethylguanidine). In an exemplary embodiment, the imidization catalyst does not include diazoles. Other useful dehydrating agents may include diacetyl oxide, butyryl oxide, benzoyl oxide, 1,3-dichlorohexylcarbodiimide, N,N-dicyclohexylcarbodiimide, benzenesulfonyl chloride, thionyl chloride and phosphorus pentachloride. In some embodiments, the dehydrating agent may also act as a catalyst to enhance the reaction kinetics of imidization. An anhydride dehydrating material is generally used that is slightly in excess of the molar amount of the amic acid groups present in the polyamic acid solution. In an exemplary embodiment, the amount of the dehydrating agent used is generally about 2.0 to 4.0 moles per equivalent of polyamic acid molecular formula unit. Typically, a considerable amount of tertiary amine catalyst is used. The ratio of these catalysts and their concentration in the polyamic acid solution will affect the imidization kinetics and film properties. A polyimide film having a substantially chemically converted polyimide may have an imidization catalyst present in the polyimide film in an amount ranging from 1 ppb to 1 wt%, 10 ppb to 0.1 wt%, or 100 ppb to 0.01 wt%.
[0039] Anti-corona composite filler
[0040] In an exemplary embodiment, the polyimide film includes an electrically insulating corona resistant composite filler.
[0041] In an exemplary embodiment, the corona-resistant composite filler may have an organic component and an inorganic ceramic oxide component, wherein the weight ratio of the organic component to the inorganic ceramic oxide component is 0.01:1 to 1:1. In some exemplary embodiments, the weight ratio of the organic component to the inorganic ceramic oxide component may be between (and optionally include) any two of the following values: 0.01:1, 0.05:1, 0.1:1, 0.2:1, 0.3:1, 0.4:1, 0.5:1, 0.6:1, 0.7, 1, 0.8, 1, 0.9:1, and 1:1. In an exemplary embodiment, at least a portion of the organic component may include an organic siloxane portion or an organic metalloxane portion (e.g., an organic zirconate, an organic titanate, an organic aluminate).
[0042] In an exemplary embodiment, the filler has an inorganic ceramic oxide component, such as a ceramic oxide of Al, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Ge, Zr, Nb, Mo, Sn, Sb, Ta, W, Pb, or Ce. In an exemplary embodiment, the inorganic ceramic oxide component may include silica, alumina, titania, zirconium oxide, iron, calcium, or a mixture thereof. In an exemplary embodiment, the inorganic ceramic oxide component includes silica, alumina, or a mixture thereof. In an exemplary embodiment, the inorganic ceramic oxide component is alumina.
[0043] In exemplary embodiments, the organic component of the anti-corona composite filler material is selected primarily to provide or improve the dispersibility of the anti-corona composite filler material in a particular solvated polymer matrix or polymer matrix precursor. In some embodiments, the organic component of the anti-corona composite filler material is selected to reduce moisture absorption on the inorganic ceramic oxide component. In optimizing the organic component for any particular solvent system selected, ordinary techniques and experiments may be required. In some exemplary embodiments, the organosiloxane portion is n-octylsilane or any structural isomer thereof. In some embodiments, the anti-corona composite filler is an inorganic ceramic oxide that does not contain an organic component. In other exemplary embodiments, the organic component is a coating on the inorganic ceramic oxide component. The organic component may or may not cover the entire surface of the inorganic ceramic oxide component.
[0044] In an exemplary embodiment, the electrically insulating anti-corona composite filler is present in an amount between and including any two of the following numbers: 5, 10, 15, 20, 25, and 30 wt %, based on the total weight of the polyimide film. In an exemplary embodiment, the anti-corona composite filler is present in an amount ranging from 5 to 30 wt %, 5 to 25 wt %, or 5 to 20 wt %, based on the total weight of the polyimide film.
[0045] In an exemplary embodiment, the anti-corona composite filler may have a median particle size of 0.1 to 5 μm, wherein at least 80%, 85%, 90%, 92%, 94%, 95%, 96%, 98%, 99% or 100% of the dispersed anti-corona composite filler is within the particle size range defined above. The median particle size can be measured using a Horiba LA-930 particle size analyzer (Horiba Instruments, Inc., Irvine, CA). DMAc can be used as a carrier fluid. In some embodiments, the anti-corona composite filler is a nanofiller. The term "nanofiller" is intended to mean a filler having at least one dimension of less than 1000 nanometers (nm) or less than 1 μm.
[0046] In an exemplary embodiment, the polyimide film further comprises a dispersant. In some embodiments, the polyimide film further comprises a dispersant in an amount ranging from 1 to 100 weight percent based on the weight of the inorganic ceramic oxide component. In some exemplary embodiments, the dispersant is selected from phosphorylated polyethers, phosphorylated polyesters, and mixtures thereof. In another exemplary embodiment, the dispersant is an alkyl alcohol ammonium salt of a polyethylene glycol ester. In another embodiment, the dispersant is selected from: Disperbyk 180, an alkyl alcohol ammonium salt of a polyethylene glycol ester; Disperbyk 111, a phosphorylated polyester; BykW-9010, a phosphorylated polyester; or mixtures thereof (all from Byk-Chemie GmBH, Wesel, Germany). In another exemplary embodiment, the dispersant is Solplus D540, a phosphorylated ethylene oxide / propylene oxide copolymer available from Lubrizol, Inc., Cleveland, OH. In yet another exemplary embodiment, the dispersant is a mixture of any of the above dispersants. In some exemplary embodiments, the dispersant is an aromatic polyamic acid or an aromatic polyimide. In another embodiment, the dispersant is a polyalkylene ether such as polybutylene glycol and polyethylene glycol. Generally, aromatic polyamic acid or aromatic polyimide has high temperature stability, so most of them will be retained in the polyimide. Dispersants such as polyalkylene ethers have low temperature stability and are mostly decomposed or burned at the temperature used in the imidization method.
[0047] Production of polyimide film
[0048] In an exemplary embodiment, the polyimide film can be produced by combining a diamine and a dianhydride (monomer or other polyimide precursor form) with a solvent to form a polyamic acid (also referred to as polyamic acid) solution. The dianhydride and the diamine can be combined in a molar ratio of about 0.90 to 1.10. The molecular weight of the polyamic acid formed therefrom can be adjusted by adjusting the molar ratio of the dianhydride and the diamine.
[0049] In an exemplary embodiment, the polyamic acid casting solution is derived from a polyamic acid solution. The polyamic acid casting solution and / or the polyamic acid solution and conversion chemicals such as: (i) one or more dehydrating agents, for example, aliphatic anhydrides (acetic anhydride, etc.) and / or aromatic anhydrides; and (ii) one or more catalysts, such as aliphatic tertiary amines (triethylamine, etc.), aromatic tertiary amines (dimethylaniline, etc.) and heterocyclic tertiary amines (pyridine, picoline, isoquinoline, etc.). Compared with the amount of the amic acid group in the polyamic acid, anhydride dehydration materials are usually used in molar excess. The amount of acetic anhydride used is usually about 2.0 to 4.0 moles per equivalent (repeating unit) of polyamic acid. Typically, a considerable amount of tertiary amine catalyst is used. The filler dispersed or suspended in a solvent as described above is then added to the polyamic acid solution.
[0050] In exemplary embodiments, the polyamic acid solution is dissolved in an organic solvent at a concentration of about 5.0 or 10 wt % to 15, 20, 25, 30, 35 or 40 wt %. In exemplary embodiments, a slurry comprising a filler is produced, wherein the solid content of the slurry is 0.1-70 wt %, 0.5-60 wt %, 1-55 wt %, 5-50 wt % or 10-45 wt %. A ball mill can be used to grind the slurry to reach a desired particle size, or a ball mill may not be used. The slurry may be filtered to remove any residual large particles or may not be filtered. The polyamic acid solution may be produced by methods well known in the art. The polyamic acid solution may be filtered, or may not be filtered. In some embodiments, the solution is mixed with a filler slurry in a high shear mixer. When a polyamic acid solution is produced with a slightly excessive amount of diamine, an additional dianhydride solution may be added to increase the viscosity of the mixture to a desired level for film casting, or may not be added. The amounts of polyamic acid solution and filler slurry can be adjusted to achieve the desired loading level in the cured film. In some embodiments, the mixture is cooled to below 10°C and mixed with the converting chemical prior to casting.
[0051] The solvated mixture (polyamic acid casting solution) can then be cast or applied to a support such as an endless belt or a rotating drum to obtain a partially imidized gel film. Alternatively, it can be cast on a polymer carrier (e.g., PET), other forms of Polyimide film (e.g. HN or E film) or other polymer carrier. The gel film can be peeled from the drum or belt, placed on a tenter frame, and cured in an oven, using convection and radiant heat to remove the solvent and complete the imidization to a solid content of greater than 98%. The film is then separated from the support under continuous heating (drying and curing), such as by tenter orientation, to provide a substantially chemically converted polyimide film.
[0052] Useful methods for producing polyimide films can be found in U.S. Pat. No. 5,166,308 and U.S. Pat. No. 5,298,331, which are incorporated herein by reference. Many variations are possible, for example:
[0053] (a) A method in which a diamine component and a dianhydride component are mixed together in advance and then the mixture is added portionwise to a solvent while stirring.
[0054] (b) A method in which a solvent is added to a stirred mixture of the diamine and dianhydride components. (The opposite of (a) above).
[0055] (c) A method in which only a diamine is dissolved in a solvent and then a dianhydride is added thereto at a ratio that allows the reaction rate to be controlled.
[0056] (d) A method in which the dianhydride component is merely dissolved in a solvent, and then the amine component is added thereto in a proportion that allows the reaction rate to be controlled.
[0057] (e) A method in which a diamine component and a dianhydride component are separately dissolved in solvents and then these solutions are mixed in a reactor.
[0058] (f) A method in which a polyamic acid having an excess of an amine component and another polyamic acid having an excess of a dianhydride component are preformed and then reacted with each other in a reactor, particularly in a manner to produce a non-random or block copolymer.
[0059] (g) A method in which a specific part of the amine component and the dianhydride component are first reacted and then the remaining diamine component is reacted, or vice versa.
[0060] (h) A method in which the conversion chemical (catalyst) is mixed with the polyamic acid to form a polyamic acid casting solution, which is then cast to form a gel film.
[0061] (i) A method wherein the components are added partly or entirely to partly or entirely of a solvent in any order, and wherein part or all of any component may be added to partly or entirely of a solvent as a solution.
[0062] (j) A method in which one of the dianhydride components is first reacted with one of the diamine components to obtain a first polyamic acid. The other dianhydride component is then reacted with the other amine component to obtain a second polyamic acid. The amic acids are then combined in any of a variety of ways before film formation.
[0063] In exemplary embodiments, first filler is dispersed in solvent to form slurry.Then slurry is dispersed in polyamic acid solution.In exemplary embodiments, the concentration of filler and polyimide (in final film) is in the scope of 10 volume % to 50 volume %, 15 volume % to 45 volume %, 15 volume % to 40 volume %, 20 volume % to 35 volume % or 25 volume % to 30 volume %.In exemplary embodiments, filler is at least 10 volume %, at least 15 volume %, at least 20 volume % or at least 25 volume % relative to the concentration of polyimide (in final film).The composition of cured film can be calculated by the composition of the component in the mixture, excludes DMAc solvent (it is removed during curing) and considers that polyamic acid is converted into the removal of water during polyimide.
[0064] In exemplary embodiments, the polyamic acid casting solution filled is a blend of polyamic acid solution and filler. In this casting solution, filler exists with a concentration of 0.1 to 70 volume %, 1 to 60 volume %, 2-50 volume %, 5 to 45 volume % or 5 to 40 volume %. In exemplary embodiments, first filler is dispersed in the same polar aprotic solvent (such as DMAc) for the production of polyamic acid solution. Alternatively, a small amount of polyamic acid solution can be added to filler slurry to increase the viscosity of slurry. Alternatively, dispersant or dispersant can be added to help disperse or change the rheology of slurry.
[0065] The filler can be blended into a particular solvated polymer matrix or polymer matrix precursor using any conventional technique, such as batch mixing with a solvent, dry mixing, or continuous mixing with a solvent. Parameters such as the order of raw material addition, mixing speed, shear rate, type of mixing blade (e.g., shear blade), mixing time, temperature, and pressure are known to affect the final degree of mixing between the filler and matrix materials.
[0066] In an exemplary embodiment, a filler slurry is blended with a polyamic acid solution using high shear mixing to form a filled polyamic acid casting solution. In such an exemplary embodiment, if the filler is present in the final film at more than 50% by volume, the film may be too brittle and may not be flexible enough to form an independent, mechanically tough flexible sheet.
[0067] In exemplary embodiments, the casting solution may further include any of a variety of additives, such as processing aids (eg, oligomers), antioxidants, light stabilizers, flame retardant additives, antistatic agents, heat stabilizers, ultraviolet absorbers, or various reinforcing agents.
[0068] In some exemplary embodiments, a coextrusion process can be used to form a multilayer polyimide film with an inner core layer sandwiched between two outer layers. In this method, the finished polyamic acid solution is filtered and pumped to a slot die, where the stream is separated in a manner of the first outer layer and the second outer layer of a three-layer coextruded film. In some embodiments, the second stream of polyimide is filtered and then pumped to a casting die in a manner of forming an intermediate polyimide core layer of a three-layer coextruded film. The flow rate of the solution can be adjusted to obtain the desired layer thickness.
[0069] In some exemplary embodiments, the multilayer film is produced by extruding the first outer layer, the core layer and the second outer layer simultaneously. In some exemplary embodiments, the layers are extruded through a single-cavity or multi-cavity extrusion die. In other exemplary embodiments, a single-cavity die is used to produce a multilayer film. If a single-cavity die is used, the laminar flow of the flow should have a sufficiently high viscosity to prevent the flow from mixing and provide uniform stratification. In some exemplary embodiments, the multilayer film is produced by casting from a slit die onto a moving stainless steel belt. In an exemplary embodiment, the belt is then passed through a convection oven to evaporate the solvent and partially imidize the polymer to produce a "green" film. The green film can be peeled off from the casting belt and wound. The green film can then be passed through a tenter oven to produce a fully cured polyimide film. In some exemplary embodiments, during the tentering process, shrinkage can be minimized by constraining the film along the edges (i.e., using clips or pins).
[0070] In an exemplary embodiment, the outer layer of the present invention may also be applied to the core layer at an intermediate production stage in producing the polyimide film, for example to a gel film or a green film.
[0071] When forming a polyimide film, the term "gel film" refers to a polyamic acid sheet that is loaded with volatiles, primarily solvents, to the extent that the polyamic acid is in a gel-swollen or rubbery state and can be formed during a chemical conversion process. The volatile content is typically 70 to 90% of the gel film weight, and the polymer content is typically 10 to 30% of the gel film weight. The final film becomes "self-supporting" at the gel film stage. It can be peeled from the support on which it is cast and heated to the final curing temperature. The ratio of amic acid to imide of the gel film is typically 10:90 to 50:50, most typically 30:70.
[0072] The gel film structure can be produced by the method described in U.S. Patent 3410826. The patent discloses mixing chemical conversion agents and catalysts such as lower fatty acid anhydrides and tertiary amines into a polyamic acid solution at low temperatures. The polyamic acid solution is then cast onto a casting drum in the form of a film. After casting, the film is gently heated at, for example, 100° C. to activate the conversion agent and catalyst, thereby converting the cast film into a polyamic acid / polyimide gel film.
[0073] Another type of polymer film is a "green film", which for polyimide films is part polyamic acid and part polyimide, and can be formed in a thermal conversion process. A green film typically contains about 50 to 75% by weight of polymer and 25 to 50% by weight of solvent. Generally, it should be strong enough to be substantially self-supporting. A green film can be produced by casting a polyamic acid solution into a film onto a suitable support such as a casting drum or belt and removing the solvent by gentle heating at up to 150°C. A low proportion of the amic acid units in the polymer, for example up to 25%, can be converted into imide units.
[0074] The application of the polyimide film in the exemplary embodiments disclosed herein can be achieved in a variety of ways. These methods include using a slot die, dip coating or kiss-roll coating film, and then metering with a scraper, scraper roller, squeeze roller or air knife. The coating can also be applied by brushing or spraying. By using this technology, single-sided and double-sided coated laminates can be produced. In the production of double-sided coated structures, the coating can be applied to both sides of the polymer simultaneously or continuously before the curing and drying stages of the polymer are performed.
[0075] Electrically insulating anti-corona composite fillers (dispersions or colloids thereof) can be added at several points in the production of polyimide films. In an exemplary embodiment, the colloid or dispersion is introduced into a prepolymer having a Brookfield solution viscosity of about 50 to 100 poise at 25°C. "Prepolymer" is intended to mean a lower molecular weight polymer, typically produced with a small stoichiometric excess (about 2 to 4%) of diamine monomer (or excess dianhydride monomer). In an alternative embodiment, the colloid or dispersion can be combined directly with the monomer, and in this case, polymerization occurs in the presence of the filler during the reaction. In another embodiment, the colloid or dispersion can be combined with a "finished" high viscosity polyimide. During this "in situ" polymerization, the monomer may have an excess of monomer (diamine or dianhydride). Monomers can also be added in a 1:1 ratio. In the case where the monomer is added with excess amine (case i) or dianhydride (case ii), an increase in molecular weight (and solution viscosity) can be achieved by adding incremental amounts of additional dianhydride (case i) or diamine (case ii) to achieve a 1:1 stoichiometric ratio of dianhydride to amine, if necessary.
[0076] The thickness of the polyimide film may be adjusted according to the intended purpose or final application specifications of the film. In exemplary embodiments, the total thickness of the polyimide film ranges from 2 to 300 μm, 5 to 200 μm, 7 to 150 μm, 10 to 100 μm, or 15 to 80 μm.
[0077] In one embodiment, one or more imidization catalysts are used to produce a single layer polyimide film that is 19 μm and contains about 17 wt % well dispersed alumina.
[0078] The polyimide film may have certain desirable properties. Desirable properties include (a) an elongation at break of 40% or more in both the longitudinal and transverse film directions, (b) a tensile strength of 20 kpsi or more, (c) a tensile modulus of 2 GPa or more, (d) a coefficient of thermal expansion of less than 60 ppm / °C in both the longitudinal and transverse film directions, (e) a dielectric strength of 3 kV / mil or more, (f) a thermal glass transition temperature of 250°C or more, (g) a thermal rating of 200°C or more, and (h) a residual volatile content (excluding water) of less than 1 wt%. The testing of these properties can be performed according to standard procedures known in the industry, such as those published by ASTM or UL.
[0079] Fluoropolymer layer
[0080] In an exemplary embodiment, a polyimide film with an electrically insulating anti-corona composite filler has a first fluoropolymer layer adhered to a first side of the polyimide. The fluoropolymer layer is used to bond the polyimide film to a metal layer, an enamel coating, or a wire, such as a rectangular electrical conductor (e.g., a rectangular copper wire, etc.). Additional fluoropolymer layers may be present on the same side as the first fluoropolymer layer or on the opposite side of the polyimide film. In other embodiments, polymers based on silicone, acrylate, epoxy, urethane, urethane-acrylate, or mixtures thereof may be adhered to the polyimide film and function similarly to the fluoropolymer layer.
[0081] In an exemplary embodiment, the base film tape comprises a polyimide film having a first fluoropolymer layer. In an exemplary embodiment, the base film tape can be used as a wrap for an electrically insulated conductor or cable comprising a rectangular electrical conductor (e.g., a rectangular copper wire, etc.). In an exemplary embodiment, the base film tape has a thickness in the range of 25 μm to 40 μm measured in an unfolded state.
[0082] In an exemplary embodiment, the fluoropolymer layer comprises a fluoropolymer selected from tetrafluoroethylene-hexafluoropropylene copolymer (FEP), perfluoroalkoxy resin (PFA), polytetrafluoroethylene (PTFE) or a mixture thereof. In an exemplary embodiment, the fluoropolymer layer comprises FEP in an amount ranging from 65 wt % to 100 wt % based on the total weight of the fluoropolymer layer. In an exemplary embodiment, the amount of FEP included in the fluoropolymer layer is between (and optionally includes) any two of the following numbers based on the total weight of the fluoropolymer layer: 65 wt %, 70 wt %, 75 wt %, 80 wt %, 85 wt %, 90 wt %, 95 wt % and 100 wt %. In an exemplary embodiment, the first fluoropolymer layer, the second fluoropolymer layer, or both the first fluoropolymer layer and the second fluoropolymer layer are in direct contact with the polyimide film, so that there is no intermediate layer between the fluoropolymer layer and the polyimide film. In an exemplary embodiment, the fluoropolymer layer comprises 100 wt % of FEP. In an exemplary embodiment, the fluoropolymer in the fluoropolymer layer is not cross-linked. In exemplary embodiments, the first fluoropolymer layer and the second fluoropolymer layer are the same or different.
[0083] The fluoropolymer layer will typically have a thickness in the range between (and optionally including) any two of the following numbers: 0.25, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.25, 1.5, 1.75, 2, 3, 4, 5, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24 and 25 μm. Useful thickness ranges are typically in the range of about 5 μm to 15 μm. In practice, the desired thickness may depend on the specification, particularly for automotive or heavy traction applications. When the fluoropolymer layer is located between the polyimide film and the electrical conductor, the thickness of the fluoropolymer layer may affect the adhesion strength of the polyimide film to the electrical conductor (bare or covered with insulating material).
[0084] In some exemplary embodiments, the fluoropolymer layer may be applied to the polyimide film by, but not limited to, solution coating, colloidal dispersion coating, extrusion, or lamination. In one embodiment, the fluoropolymer is coated or laminated onto a polyimide film that has previously been surface modified to improve adhesion.
[0085] The polyimide film may have its surface modified to improve adhesion to other layers such as fluoropolymer layers. Examples of useful surface modifications are, but are not limited to, corona treatment, plasma treatment at atmospheric pressure, plasma treatment at reduced pressure, treatment with coupling agents such as silanes and titanates, sandblasting, alkali treatment, and acid treatment.
[0086] The fluoropolymer layers of the present disclosure may contain flame retardants and thermally conductive fillers, as well as fillers that adjust the opacity, color, and rheology of the fluoropolymer layer.
[0087] In some exemplary embodiments, the fluoropolymer layer may include an inorganic filler, such as silicon dioxide, aluminum oxide, titanium dioxide and / or zirconium oxide. The filler may be the same as or different from the filler present in the polyimide film. The filler may be present in a range of 1 to 10 wt % relative to the dry weight of the coating. If more than one fluoropolymer layer is present on the polyimide film, each fluoropolymer layer may be independently filled or unfilled.
[0088] Wire winding process
[0089] In an exemplary embodiment, an electrically insulating film with an electrically insulating anti-corona composite filler can be used as a wire wrap. Suitable materials for wrapping include bare conductors, conductors covered with enamel, conductors covered with extruded resins, or conductors covered with film tapes. In some exemplary embodiments, the wire wrap may include additional layers, such as adhesive layers or wear layers. The film or sheet of the wrapped conductor can be cut into narrow widths to provide a tape. The specific width of the tape is selected according to the size of the conductor to be wrapped. These tapes can be wound around the conductor in a spiral or overlapping manner. The amount of tape overlap can vary depending on the angle of the wrap. In an exemplary embodiment, the overlap does not exceed 70%. The tension used during the wrapping operation can also vary over a wide range, from a tension just enough to prevent wrinkling to a high tension sufficient to stretch and neck the tape. Even when the tension is low, tight wrapping is possible because the tape will generally shrink under the influence of heat during any subsequent heat sealing operation. The heat sealing of the tape can be achieved by treating the conductor wrapped with the tape at a temperature and time sufficient to fuse the adhesive layer to other layers in the composite material. The required heat sealing temperature is generally in the range of 240, 250, 275, 300, 325 or 350° C. to 375, 400, 425, 450, 475 or 500° C., depending on the insulation thickness, the gauge of the metal conductor, the speed of the production line and the length of the seal. In the case where there is only one fluoropolymer layer on the polyimide film, the fluoropolymer layer in the tape preferably faces the electrical conductor. Parameters such as the absolute humidity level and temperature of the surrounding atmosphere, wire tension, wrap angle, heating and cooling rates, and the manner in which heat (e.g., convection, radiation or induction) and pressure are applied can affect the properties of the final wire insulation material.
[0090] The wound electrical conductor may have certain desirable properties. Desirable properties include (a) a visible appearance that is free of defects such as blisters or bubbles or wrinkles or lifted tape edges, (b) a thermal rating of 200°C or higher when applied to copper, (c) a residual solvent content of 1 wt% or less, (d) a breakdown voltage value of at least 2 kV or higher that is retained to at least 50% of its initial value after the wound conductor is elongated by at least 5%, bent, chemically exposed, or thermally exposed, (e) no visible damage when bent edgewise or flat by rotating 180° about a mandrel having a diameter twice the conductor width, (f) a thermal rating of at least 200°C or higher when applied to copper, (g) a thermal rating of at least 200°C or higher when applied to copper, (h ...c) a residual solvent content of at least 1 wt% or less, (d) a breakdown voltage value of at least 2 kV or higher that is retained to at least 50% of its initial value after the wound conductor is elongated by at least 5%, bent, chemically exposed, or thermally exposed, (e) no visible damage when bent edgewise or flatwise by rotating 180° about a mandrel having a diameter twice the conductor width, (f) a thermal rating of at least 200°C or higher when exposed to at least 200°C for at least 30 minutes or when otherwise first bent along an edge or flat edge or when otherwise first elongated to at least 10%, no visible damage, (g) an elongation at break of at least 30%, (h) after elongation of at least 20% or when otherwise first heat aged at at least 150°C for at least 30 minutes, the loss of adhesion of the insulating material is less than 1 times the conductor width, (i) a certain static friction coefficient, (j) a certain partial discharge inception voltage at a threshold of 20 pico-coulombs above 700V under ambient conditions, and (k) a certain abrasion / scratch resistance. Testing of these properties can be carried out according to standard procedures known in the industry such as IEC 60851, ASTM or ANSI / NEMA MW 1000.
[0091] Conductor performance data
[0092] Table 1 below includes a comparison of the partial discharge initiation voltage (PDIV) (the voltage at or above which the partial discharge phenomenon begins to occur within the wire insulation) between PAI (polyamide-imide) enamel, PAEK (having a glass transition point of about 140°C to 150°C) with a primer bottom layer (e.g., PAI enamel), and three samples produced by the dual-layer scheme disclosed herein. Table 1 also includes a comparison of their temperature dependence. In Table 1 below, Vrms is the root mean square voltage, OL is the overlap percentage, and RT indicates an ambient temperature in the range of 19°C to 25°C.
[0093] Table 1
[0094]
[0095] Overall, the results shown in Table 1 above indicate that the dual-layer approach produces average PDIV values similar to existing wire insulation approaches. In addition, for the dual-layer insulation approach, the drop in PDIV values at higher temperatures is similar or less severe than the drop in PDIV values for other existing wire insulation approaches.
[0096] Each sample in Table 1 comprises a rectangular copper conductor having a size of about 2 mm x 4 mm and a corner radius of about 0.5 mm. The first sample (PAI enameled) comprises a rectangular copper conductor coated with a polyamide-imide (PAI) enameled coating having an average thickness of 80 μm per side. The insulation thickness is determined according to IEC 60851-2.
[0097] The second sample (PAEK with primer) comprises a rectangular copper conductor first coated with a PAI enamel coating having an average thickness of 40 to 50 μm per side, and a subsequent extruded layer of PAEK (with a glass transition point of about 140° C. to 150° C.) having an average thickness of 160 μm per side. The third, fourth and fifth samples (two-layer embodiments) comprise rectangular copper conductors first coated with a PAI enamel coating having an average thickness of 60 to 65 μm / side, and then wrapped with tape and heat sealed to obtain a total average thickness of 93 μm (20% overlap (OL) or 125 μm (53% or 66% OL) / side). The insulation thickness is determined according to IEC 60851-2. The tape used in all two-layer embodiments is a 20 to 22 μm thick single layer polyimide film (containing monomers ODA and PMDA and about 16 to 17 wt % well dispersed alumina) that has been surface treated and then laminated on one side to a single FEP based polymer film about 11 to 13 μm thick. The FEP layer faces the conductor during the winding process.
[0098] The test conditions included determination of PDIV values according to ASTM D 1868 with an AC power supply, with samples arranged in a "strip-to-strip" line test configuration, using 20 pico-coulombs as the selected threshold for PD activity.
[0099] Table 2 below includes average PDIV and dielectric breakdown values (at RT) for dual layer constructions at RT and elevated temperature (180°C) as a function of enamel composition.
[0100] Table 2
[0101]
[0102] Each sample comprises a rectangular copper conductor having a size of about 2 mm x 4 mm and a corner radius of about 0.5 mm. The average thickness of the polyimide (PI) enamel is 40-45 μm per side, the average thickness of the PAI enamel is 60-65 μm per side, and the average thickness of the polyester-imide / polyamide-imide (PEI / PAI) enamel is 60-65 μm per side. Each rectangular copper conductor with the enamel coated thereon is then wrapped and heat sealed with the indicated overlap percentage (% OL). The insulation thickness is determined according to IEC 60851-2.
[0103] The test conditions included determination of average PDIV values with an AC power supply according to ASTM D 1868, with samples arranged in a "strip-to-strip" line test configuration, using 20 pico-coulombs as the threshold for PD activity. Dielectric breakdown values were determined according to IEC 60851-5, using a steel ball bath.
[0104] Table 3 below includes a comparison of average durability life between enamel packages, PAEK and primer, and the dual-layer solution of the present application.
[0105] Table 3
[0106] sample Average insulation thickness per side [μm] Average withstand voltage life [hours] PAI lacquer bag 80 0.45 PEEK+PAI enamel 200 0.60 Double layer (53% OL) 123 56.5 Double layer (20% OL) 91 0.73
[0107] Each sample includes a rectangular copper wire with a size of about 2mm×4mm and a corner radius of about 0.5mm. In the first sample, the average thickness of the PAI enamel is 80μm per side. For the second sample (PAEK with primer), the first PAI enamel primer layer is 40 to 50μm thick on average per side, and the upper extrusion layer of PAEK (with a glass transition point of about 140°C to 150°C) is 160μm thick on average per side. The third and fourth samples (double layers) include polyamide-imide enamels with an average thickness of 60-65μm per side, and these samples are then tape-wrap to achieve a total average thickness of 123μm (53% OL) or 91μm (20% OL) per side after heat sealing. Insulation thickness is determined according to IEC 60851-2.
[0108] The test conditions included a bipolar square wave pulse durability tester, an applied voltage of 1.5 kV peak-to-peak at 180°C, a frequency of 20 kHz, a voltage rise time of 14 ns, and a peak voltage time of 50 ns.
[0109] Table 4 below includes the average durability life of the two-layer structure as a function of the enamel composition.
[0110] Table 4
[0111] sample Average insulation thickness per side [μm] Average withstand voltage life [hours] Double layer (PI enameled, 53% OL) 108 5.9 Double layer (PI enameled, 15% OL) 75 0.67 Double layer (PAI enamel, 53% OL) 123 56.5 Double layer (PAI enamel, 20% OL) 91 0.73 Double layer (PEI / PAI enamel, 53% OL) 125 >110
[0112] Each sample includes a rectangular copper wire with a size of about 2mm×4mm and a corner radius of about 0.5mm. In the first sample and the second sample, the average thickness of the PI enamel is 40-45μm on each side. In the third sample and the fourth sample, the average thickness of the PAI enamel is 60-65μm on each side. In the fifth sample, the average thickness of the PEI / PAI enamel is 60-65μm on each side. Each wire is wound to obtain the total average thickness and overlap percentage (%OL) and heat sealed. Determine the insulation thickness according to IEC 60851-2.
[0113] The test conditions included a bipolar square wave pulse durability tester, an applied voltage of 1.5 kV peak-to-peak at 180°C, a frequency of 20 kHz, a voltage rise time of 14 ns, and a peak voltage time of 50 ns.
[0114] Adhesion and elongation at break testing
[0115] According to IEC 60851-3, adhesion and elongation tests were performed on the wire samples.
[0116] Elongation at break test: Elongation at break greater than 30% was observed for wire samples with bare copper conductor size of approximately 2 mm x 4 mm, corner radius of approximately 0.5 mm, PAI enamel coating with an average thickness of 60 μm per side and tape overlap in the range of 20 to 66%. Insulation thickness was determined according to IEC 60851-2.
[0117] Adhesion Test: For identical wire samples with tape overlap ranging from 20 to 66%, the length along the wire at which adhesion loss occurred after elongating a single wire sample to 20% was <1 mm at <50% OL and <2 mm at 66% OL.
[0118] Adhesion testing after heat aging
[0119] The wire samples were subjected to 180°C continuously in a convection oven for 168 hours and then evaluated for adhesion behavior according to IEC 60851-3.
[0120] For a bare copper wire measuring about 2 mm x 4 mm, with a corner radius of about 0.5 mm, a PAI enamel coating with an average thickness of 60 μm per side and a wire sample with 53% tape overlap, the length along the wire where adhesion loss occurs after the sample is elongated to 20% is <2 mm. Insulation thickness is determined according to IEC 60851-2.
[0121] Bending test
[0122] Conductor samples with an average thickness of 60 μm PAI enamel coating and a tape overlap in the range of 20 to 53% were bent 180° around a mandrel with a diameter of 2x conductor width (according to IEC 60851-3.5). In individual cases, the bending was performed along the edge or along the plane. No exposed conductor material was visually observed on the conductor sample in the area subjected to the bending process. The insulation thickness was determined according to IEC 60851-2.
[0123] The exemplary embodiments disclosed herein are not limited to use with only electric motors of electric vehicles. The exemplary embodiments disclosed herein can be used in a wide range of electronic devices, including power electronics for aircraft, ships, industry, automobiles, etc., electric motors driven by pulse width modulation inverters, high switching frequency converters providing signals with high levels of dv / dt, traction electric motors for e-mobility applications, other windings driven by converter devices, etc.
[0124] Disclosed herein are exemplary embodiments of electrically insulated conductors and exemplary methods for electrically insulated conductors, such that the resulting electrically insulated conductors are resistant to partial discharge (PD), thereby being suitable for PD-resistant designs (e.g., electric motors above 800V, etc.). The exemplary method includes applying an enameled coating along the electrical conductor, wrapping an electrical insulating tape around the fully enameled electrical conductor, and heat-sealing the enameled electrical conductor wrapped with the tape to help ensure good adhesion of the electrical insulating tape to the enameled coating. The electrical insulating tape includes polyimide, an additional polymer adhered to the polyimide, and an electrically insulating anti-corona filler in an amount sufficient to resist PD. The enameled electrical conductor wrapped with the tape is resistant to partial discharge (PD), such as being suitable for stator windings of electric motors above 800V, etc.
[0125] In an exemplary embodiment, the electrically insulating tape includes about 17 weight percent of an electrically insulating anti-corona composite filler in polyimide. For example, the electrically insulating anti-corona composite filler may include aluminum oxide.
[0126] In an exemplary embodiment, the average thickness of the enamel coating is about 90 microns or less per side. For example, the average thickness of the enamel coating per side may be in the range of about 30 microns to about 80 microns.
[0127] In an exemplary embodiment, the electrically insulating tape is wrapped around the enameled electrical conductor with a tape overlap in a range of about 15% to about 70%.
[0128] In an exemplary embodiment, the total average thickness per side of the tape wrapped enameled electrical conductor, as defined by the electrical conductor, enameled coating, and electrically insulating tape, is less than about 170 microns.
[0129] In an exemplary embodiment, the electrical conductor has a uniform insulation thickness as defined by the enamel coating and the electrical insulation tape, and no handling solvents are required during the tape wrapping step.
[0130] In an exemplary embodiment, the enamel coating beneath the electrically insulating tape is configured to provide adequate electrical insulation to the electrical conductor when the electrically insulating tape is peeled and / or scraped away from the enameled electrical conductor around which the tape is wrapped.
[0131] In an exemplary embodiment, the enamel coating comprises: a polyamide-imide (PAI) enamel coating; or a polyimide (PI) enamel coating; or a polyester-imide / polyamide-imide (PEI / PAI) enamel. In such an exemplary embodiment, the exemplary method comprises applying a polyamide-imide (PAI) enamel coating along an electrical conductor; or applying a polyimide (PI) enamel coating along the electrical conductor; or applying a polyester-imide / polyamide-imide (PEI / PAI) enamel coating along an electrical conductor.
[0132] In an exemplary embodiment, the electrical conductor comprises a copper wire, an aluminum wire, or a stainless steel wire having a generally rectangular cross-sectional shape with rounded corners. In such an exemplary embodiment, the exemplary method comprises applying a polyamide-imide (PAI) enamel coating along the copper wire, the aluminum wire, or the stainless steel wire, such that the PAI enamel coating has an average thickness in the range of about 60 microns to about 65 microns per side; wrapping an electrical insulating tape around the enameled electrical conductor comprises wrapping the electrical insulating tape around the PAI enameled copper wire, the aluminum wire, or the stainless steel wire, such that: as defined by the PAI enamel coating and the electrical insulating tape, the tape overlap is about 66%, and the average insulation thickness per side is about 125 microns; or as defined by the PAI enamel coating and the electrical insulating tape, the tape overlap is about 53% and the average insulation thickness per side is about 123 microns; or as defined by the PAI enamel coating and the electrical insulating tape, the tape overlap is about 20%, and the average insulation thickness per side is about 91 microns.
[0133] In an exemplary embodiment, the electrical conductor comprises a copper wire, an aluminum wire, or a stainless steel wire having a generally rectangular cross-sectional shape with rounded corners. In such an exemplary embodiment, an exemplary method comprises applying an enameled coating along the electrical conductor, comprising applying a polyimide (PI) enameled coating along the copper wire, the aluminum wire, or the stainless steel wire, such that the PI enameled coating has an average thickness in the range of about 40 microns to about 45 microns per side; and wrapping an electrical insulating tape around the enameled electrical conductor comprises wrapping an electrical insulating tape around the PI enameled copper wire, the aluminum wire, or the stainless steel wire, such that: as defined by the PI enameled coating and the electrical insulating tape, the tape overlap is about 53%, and the average insulation thickness per side is about 108 microns; or as defined by the PI enameled coating and the electrical insulating tape, the tape overlap is about 15% and the average insulation thickness per side is about 75 microns.
[0134] In an exemplary embodiment, the electrical conductor comprises a copper wire, an aluminum wire, or a stainless steel wire having a generally rectangular cross-sectional shape with rounded corners. In such an exemplary embodiment, an exemplary method comprises applying an enameled coating along the electrical conductor, comprising applying a polyester-imide / polyamide-imide (PEI / PAI) enameled coating along the copper wire, the aluminum wire, or the stainless steel wire, such that the PEI / PAI enameled coating has an average thickness in the range of about 60 microns to about 65 microns per side; and wrapping an electrical insulating tape around the enameled electrical conductor comprises wrapping an electrical insulating tape around the PEI / PAI enameled copper wire, the aluminum wire, or the stainless steel wire, such that the tape overlap is about 53%, and the average insulation thickness per side is about 125 microns as defined by the PEI / PAI enameled coating and the electrical insulating tape.
[0135] In an exemplary embodiment, an exemplary method includes applying an enamel coating along an electrical conductor, including applying a polyamide-imide (PAI) enamel coating along the electrical conductor such that the PAI enamel coating has an average thickness in a range of about 60 microns to about 65 microns per side; and wrapping an electrical insulating tape around the enameled electrical conductor including wrapping the electrical insulating tape around the PAI enameled electrical conductor such that the tape overlaps in a range of about 20% to about 66% and the insulation average thickness is in a range of about 91 microns to about 125 microns on each side defined by the PAI enamel coating and the electrical insulating tape.
[0136] In an exemplary embodiment, an exemplary method includes applying an enameled coating along an electrical conductor, including applying a polyimide (PI) enameled coating along the electrical conductor such that the PI enameled coating has an average thickness in a range of about 40 microns to about 45 microns on each side; and wrapping an electrical insulating tape around the enameled electrical conductor, including wrapping the electrical insulating tape around the PI enameled electrical conductor such that the tape overlaps in a range of about 15% to about 53%, and the insulation average thickness is in a range of about 75 microns to about 108 microns on each side defined by the PI enameled coating and the electrical insulating tape.
[0137] In an exemplary embodiment, an exemplary method includes applying an enamel coating along an electrical conductor, including applying a polyester-imide / polyamide-imide (PEI / PAI) enamel coating along the electrical conductor such that the PEI / PAI enamel coating has an average thickness in a range of about 50 microns to about 70 microns per side; and wrapping an electrical insulating tape around the enameled electrical conductor includes wrapping an electrical insulating tape around the PEI / PAI enameled electrical conductor such that the tape overlaps in a range of about 15% to about 70%, and the PEI / PAI enameled electrical conductor wrapped with tape has a total thickness of less than about 170 microns per side.
[0138] In an exemplary embodiment, an exemplary method includes applying an enameled coating along an electrical conductor, including applying a polyamide-imide (PAI) enameled coating along the electrical conductor such that the PAI enameled coating has an average thickness in a range of about 50 microns to about 70 microns per side; and wrapping an electrical insulating tape around the enameled electrical conductor including wrapping the electrical insulating tape around the enameled electrical conductor such that the tape overlaps in a range of about 15% to about 70%, and the enameled electrical conductor wrapped with the tape has a total thickness of less than about 170 microns per side.
[0139] In an exemplary embodiment, an exemplary method includes applying an enameled coating along an electrical conductor, including applying a polyimide (PI) enameled coating along the electrical conductor such that the PI enameled coating has an average thickness in a range of about 50 microns to about 70 microns per side; and wrapping an electrical insulating tape around the enameled electrical conductor, including wrapping the electrical insulating tape around the PI enameled electrical conductor such that the tape overlaps in a range of about 15% to about 70%, and the PI enameled electrical conductor wrapped with the tape has a total thickness of less than about 170 microns per side.
[0140] In an exemplary embodiment, the enamel coating along the electrical conductor includes a polyamide-imide (PAI) enamel coating including 4,4'-methylenedianiline and trimellitic anhydride.
[0141] In an exemplary embodiment, an electrical insulating tape includes a polyimide film including pyromellitic dianhydride (PMDA) and 4,4'-diaminodiphenyl ether (ODA).
[0142] In an exemplary embodiment, the electrical insulating tape includes about 10% to 25% by weight of an electrically insulating anti-corona composite filler in a polyimide. The electrical insulating tape has a thickness of less than 30 microns, excluding additional polymers adhered to the polyimide. In such an exemplary embodiment, an exemplary method includes applying an enamel coating along an electrical conductor, including applying a polyamide-imide (PAI) enamel coating along the electrical conductor, so that the PAI enamel coating has an average thickness in the range of about 30 microns to about 80 microns per side; and wrapping the electrical insulating tape around the enameled electrical conductor includes wrapping the electrical insulating tape around the enameled electrical conductor so that the tape overlaps in the range of about 15% to about 70%, and the enameled electrical conductor wrapped with the tape has a total thickness of less than about 170 microns per side. The PAI enamel coating may include 4,4'-methylenedianiline and trimellitic anhydride. And the electrical insulating tape may include a polyimide film, the polyimide film including pyromellitic dianhydride (PMDA) and 4,4'-diaminodiphenyl ether (ODA).
[0143] In an exemplary embodiment, the tape-wound enameled electrical conductor is configured so that the tape-wound enameled electrical conductor has one or more of the following: (a) a visible appearance that is free of defects such as blisters or bubbles or wrinkles or lifted tape edges; (b) a thermal rating of 200°C or higher when applied to copper; (c) a residual solvent content of 1 wt% or lower; (d) a breakdown voltage value of at least 2 kV or higher, and the breakdown voltage value is retained at least 50% of the initial value after the wrapped conductor is elongated by at least 5%, bent, chemically exposed or thermally exposed; (e) when bent edgewise or rotated 180° around a mandrel having a diameter twice the conductor width, the conductor is , no visible damage; (f) no visible damage when exposed to at least 200°C for at least 30 minutes, or when otherwise first bent flat or edgewise, or when otherwise first elongated to at least 10%, (g) an elongation at break of at least 30%; (h) after elongation of at least 20% or when otherwise first heat aged at at least 150°C for at least 30 minutes, the adhesion loss of the insulating material is less than 1 times the conductor width; (i) a certain static friction coefficient; (j) a certain partial discharge inception voltage at a threshold of 20 pico-coulombs above 700V under ambient conditions; and / or (k) a certain wear resistance / scratch resistance.
[0144] In an exemplary embodiment, the enameled electrical conductor prior to tape wrapping is configured such that the enameled electrical conductor has one or more of the following: (a) a visible appearance of an enameled package without defects such as blisters or bubbles; (b) a thermal rating of 200°C or higher when the enameled package is applied to copper; (c) a residual solvent content of 5 wt% or lower; (d) a breakdown voltage value of at least 2 kV or higher, and the breakdown voltage value remains at least 50% of the initial value after the conductor is elongated by at least 5%, bent, chemically exposed or thermally exposed; (e) no visible cracks when bent edgewise or rotated 180° around a mandrel having a diameter twice the conductor width; (f) a dielectric strength of at least 2 kV or higher, and ... f) no visible cracking when exposed to at least 200°C for at least 30 minutes, or when otherwise first bent flat or edgewise, or when otherwise first elongated to at least 10%, (g) an elongation at break of at least 30%, (h) when otherwise first heat aged at at least 150°C for at least 30 minutes, after elongation of at least 20%, or when otherwise first heat aged for at least 30 minutes, the loss of adhesion of the enamel is less than 1 times the conductor width, (i) a certain static friction coefficient, (j) a certain partial discharge inception voltage at a threshold of 20 pico-coulombs above 700V under ambient conditions, and (k) a certain wear / scratch resistance.
[0145] In an exemplary embodiment, the electrical insulating tape includes a polyimide film configured such that the polyimide film has one or more of the following: (a) an elongation at break of 40% or more in both the longitudinal and transverse film directions; (b) a tensile strength of 20 kpsi or more; (c) a tensile modulus of 2 GPa or more; (d) a coefficient of thermal expansion in the longitudinal and transverse film directions of less than 60 ppm / °C; (e) a dielectric strength of 3 kV / mil or more; (f) a thermal glass transition temperature of 250°C or more; (g) a thermal rating of 200°C or more; and (h) a residual volatile content (excluding water) of less than 1 wt %.
[0146] In an exemplary embodiment, the electrical conductor comprises magnet wire and / or copper, aluminum or stainless steel wire having a generally rectangular, circular, oval, rhomboid, hollow or rounded rectangular cross-sectional shape.
[0147] In an exemplary embodiment, the electrical conductor comprises a copper wire, an aluminum wire or a stainless steel wire having a generally rectangular cross-sectional shape with rounded corners; and / or the electrical conductor has a generally rectangular cross-sectional shape with dimensions of approximately 1 to 6 mm x 1.5 to 20 mm, with a corner radius of less than 1 mm, or dimensions of approximately 1 to 20 mm x 20 to 200 mm, with a corner radius of 0.1 to 3 mm.
[0148] In an exemplary embodiment, an exemplary method includes curing the enameled coating prior to wrapping the electrical insulating tape around the enameled electrical conductor.
[0149] In an exemplary embodiment, the tape-wound enameled electrical conductor is suitable for use in stator windings of electric motors above 800V.
[0150] In an exemplary embodiment, a stator winding for an electric motor above 800V includes a tape-wound enameled electrical conductor as disclosed herein.
[0151] Exemplary embodiments are provided so that the present disclosure will be thorough and will fully convey its scope to those skilled in the art. Many specific details, such as examples of specific components, devices, and methods, are set forth to provide a thorough understanding of the embodiments of the present disclosure. It will be apparent to those skilled in the art that specific details need not be adopted, that the exemplary embodiments may be embodied in many different forms, and that they should not be construed as limiting the scope of the present disclosure. In some example embodiments, well-known processes, well-known device structures, and well-known techniques are not described in detail. In addition, the advantages and improvements that may be achieved by one or more exemplary embodiments of the present disclosure are provided for illustrative purposes only and do not limit the scope of the present disclosure, because the exemplary embodiments disclosed herein may provide all or none of the above-mentioned advantages and improvements and still fall within the scope of the present disclosure.
[0152] The specific numerical dimensions and values, specific materials and / or specific shapes disclosed herein are exemplary in nature and do not limit the scope of the present disclosure. The disclosure of the specific value and specific value range of a given parameter herein does not exclude other values and value ranges that can be used in one or more examples disclosed herein. In addition, it is envisioned that any two specific values of a specific parameter described herein can define the endpoints of the value range applicable to a given parameter (the disclosure of the first value and the second value for a given parameter can be interpreted as disclosing that any value between the first value and the second value can also be adopted for a given parameter). For example, if parameter X is exemplified herein as having value A and also exemplified as having value Z, it is envisioned that parameter X can have the range of values from about A to about Z. Similarly, it is envisioned that the disclosure of two or more ranges of the value of a parameter (whether such ranges are nested, overlapped or different) includes all possible combinations of the range of values that may be required using the endpoints of the disclosed range. For example, if parameter X is illustrated herein as having values in the range of 1 to 10, or 2 to 9, or 3 to 8, it is also contemplated that parameter X may have other ranges of values including 1 to 9, 1 to 8, 1 to 3, 1 to 2, 2 to 10, 2 to 8, 2 to 3, 3 to 10, and 3 to 9.
[0153] The terms used herein are only used for the purpose of describing specific exemplary embodiments and are not intended to be limiting. As used herein, the singular forms "one", "a kind of" and "the" may also be intended to include plural forms unless the context clearly indicates otherwise. The terms "include", "comprise", "contain", "have", "have" and "contain" are inclusive, and therefore specify the presence of the features, integers, steps, operations, elements and / or components, but do not exclude the presence or addition of one or more other features, integers, steps, operations, elements, components and / or combinations thereof. The method steps, processes and operations described herein should not be interpreted as necessarily requiring them to be performed in the specific order discussed or shown, unless explicitly identified as an execution order. It should also be understood that additional or alternative steps may be adopted.
[0154] When an element or layer is referred to as being "on another element or layer," "engaged to another element or layer," "connected to another element or layer," or "coupled to another element or layer," it may be directly on, engaged, connected, or coupled to another element or layer, or there may be intervening elements or layers. Conversely, when an element is referred to as being "directly on another element or layer," "directly engaged to another element or layer," "directly connected to another element or layer," or "directly coupled to another element or layer," there may be no intervening elements or layers. Other words used to describe the relationship between elements should be interpreted in a similar manner (e.g., "between" versus "directly between," "adjacent" versus "directly adjacent," etc.). As used herein, the term "and / or" includes any and all combinations of one or more of the associated listed items.
[0155] When applied to a value, the term "about" means that the calculation or measurement allows some slight imprecision in the value (some precision in the value is close; close to or reasonably close to the value; near). If for some reason, the imprecision provided by "about" is not understood in this ordinary sense in the art, then "about" as used herein at least represents the variation that can be caused by the ordinary method of measuring or using such parameters. For example, the terms "generally", "about" and "substantially" can be used herein to indicate within manufacturing tolerances. Or, for example, when modifying the amount or use of the ingredients or reactants of the present invention, the term "about" as used herein refers to the variation of the numerical amount that can occur through the typical measurement and processing procedures used, for example, when concentrates or solutions are produced in the real world through unintentional errors in these procedures; by differences in the production, source or purity of the ingredients used to produce the composition or implement the method; and so on. The term "about" also covers different amounts due to different equilibrium conditions of the composition produced by a specific initial mixture. Whether or not modified by the term "about", the claim includes equivalents of the amount.
[0156] Although the terms first, second, third, etc. can be used here to describe various elements, components, regions, layers and / or parts, these elements, components, regions, layers and / or parts should not be limited by these terms. These terms can only be used to distinguish an element, component, region, layer or part from another region, layer or part. Terms such as "first", "second" and other numerical terms do not imply order or sequence when used in this article unless the context clearly indicates. Therefore, the first element, component, region, layer or part can be referred to as the second element, component, region, layer or part, without departing from the teaching of exemplary embodiments.
[0157] Spatially relative terms, such as "inside," "outside," "below," "lower," "above," "on," and the like, may be used herein to describe the relationship of one element or feature to another element or feature. Spatially relative terms may include different orientations of the device in use or operation. For example, if the device is turned over, an element described as being "below" or "below" other elements or features will be oriented "above" the other elements or features. Thus, the exemplary term "below" may include both above and below orientations. The device may be oriented in other ways (rotated 90 degrees or in other orientations), and the spatially relative descriptors used herein are interpreted accordingly.
[0158] The foregoing description of the embodiments has been provided for the purpose of illustration and description. It is not intended to be exhaustive or to limit the present disclosure. The individual elements, intended or stated uses or features of a particular embodiment are generally not limited to the particular embodiment, but are interchangeable and can be used in selected embodiments when applicable, even if not explicitly shown or described. They can also be varied in many ways. Such variations should not be considered as departing from the present disclosure, and all such modifications are intended to be included within the scope of the present disclosure.
Claims
1. A method for electrically insulating a conductor to render the resulting electrically insulated conductor resistant to partial discharge (PD), the method comprising: applying an enamel coating along an electrical conductor; wrapping an electrically insulating tape around the enameled electrical conductor, the electrically insulating tape comprising a polyimide, an additional polymer adhered to the polyimide, and an electrically insulating anti-corona filler in an amount sufficient to protect against PD; and heating the enameled electrical conductor around which the tape is wrapped to help ensure good adhesion of the electrical insulating tape to the enameled coating; The tape-wrapped enameled electrical conductor is thus resistant to PD.
2. The method according to claim 1, wherein: The electrically insulating tape comprises about 17 weight percent of an electrically insulating anti-corona composite filler in the polyimide; and / or The electrically insulating corona-resistant composite filler comprises aluminum oxide.
3. The method according to claim 1, wherein: The method includes: wrapping the electrical insulating tape around the enameled electrical conductor with a tape overlap in the range of about 15% to about 70%; said tape wrapped enameled electrical conductor having an overall average thickness of less than about 170 microns per side as defined by said electrical conductor, said enameled coating and said electrically insulating tape; and The enamel coating has an average thickness of less than about 90 microns per side.
4. The method according to claim 1, wherein: The method provides the electrical conductor with a uniform insulation thickness defined by the enamel coating and the electrical insulating tape and does not require handling solvents during the tape winding step; The method includes: curing the enamel coating before wrapping the electrical insulation tape around the enameled electrical conductor; and The enamel coating beneath the electrical insulating tape is configured to provide adequate electrical insulation to the electrical conductor when the electrical insulating tape is peeled and / or scraped away from the tape-wrapped enameled electrical conductor.
5. The method according to claim 1, wherein: The enamel coating along the electrical conductor comprises a polyamide-imide (PAI) enamel coating comprising 4,4'-methylenedianiline and trimellitic anhydride; and / or The electrical insulating tape includes a polyimide film including pyromellitic dianhydride (PMDA) and 4,4′-diaminodiphenyl ether (ODA).
6. The method according to any one of claims 1 to 5, wherein: Applying the enamel coating along the electrical conductor comprises: applying a polyamide-imide (PAI) enamel coating along the electrical conductor; or applying a polyimide PI enamel coating along the electrical conductor; or A polyester-imide / polyamide-imide PEI / PAI enamel coating is applied along the electrical conductor.
7. The method according to any one of claims 1 to 5, wherein: The electrical conductor comprises a copper wire, an aluminum wire or a stainless steel wire having a substantially rectangular cross-sectional shape with rounded corners; Applying the enamel coating along the electrical conductor includes: applying a polyamide-imide (PAI) enamel coating along the copper, aluminum, or stainless steel conductor such that the PAI enamel coating has an average thickness in a range of about 60 microns to about 65 microns per side; and Winding the electrical insulation tape around the enameled electrical conductor includes: winding the electrical insulation tape around a PAI enameled copper wire, an aluminum wire, or a stainless steel wire, such that: The tape overlap is about 66% and the average insulation thickness per side as defined by the PAI enamel coating and the electrically insulating tape is about 125 microns; or The tape overlap is about 53% and the average insulation thickness per side as defined by the PAI enamel coating and the electrically insulating tape is about 123 microns; or The tape overlap was about 20%, and the average insulation thickness per side, as defined by the PAI enamel coating and the electrical insulation tape, was about 91 microns.
8. The method according to any one of claims 1 to 5, wherein: The electrical conductor comprises a copper wire, an aluminum wire or a stainless steel wire having a substantially rectangular cross-sectional shape with rounded corners; Applying the enamel coating along the electrical conductor comprises: applying a polyimide PI enamel coating along the copper wire, aluminum wire or stainless steel wire such that the PI enamel coating has an average thickness in a range of about 40 microns to about 45 microns per side; and Winding the electrical insulation tape around the enameled electrical conductor includes: winding the electrical insulation tape around a PI enameled copper wire, an aluminum wire or a stainless steel wire, so that: The tape overlap is about 53% and the average insulation thickness per side as defined by the PI enamel coating and the electrical insulating tape is about 108 microns; or The tape overlap was about 15%, and the average insulation thickness per side, as defined by the PI enamel coating and the electrical insulation tape, was about 75 microns.
9. The method according to any one of claims 1 to 5, wherein: The electrical conductor comprises a copper wire, an aluminum wire or a stainless steel wire having a substantially rectangular cross-sectional shape with rounded corners; Applying the enamel coating along the electrical conductor comprises: applying a polyester-imide / polyamide-imide PEI / PAI enamel coating along the copper wire, aluminum wire or stainless steel wire such that the PEI / PAI enamel coating has an average thickness in a range of about 60 microns to about 65 microns per side; and Wrapping the electrical insulation tape around the enameled electrical conductor includes wrapping the electrical insulation tape around a PEI / PAI enameled copper, aluminum or stainless steel conductor such that the tape overlap is about 53% and the average insulation thickness per side is about 125 microns as defined by the PEI / PAI enameled coating and the electrical insulation tape.
10. The method according to any one of claims 1 to 5, wherein: The method comprises applying a polyamide-imide (PAI) enamel coating along the electrical conductor and wrapping the electrical insulation tape around the PAI enamel electrical conductor such that: said PAI enamel coating having an average thickness per side in the range of about 60 microns to about 65 microns, with a tape overlap in the range of about 20% to about 66%, and said average insulation thickness per side as defined by said PAI enamel coating and said electrically insulating tape in the range of about 91 microns to about 125 microns; or The PAI enamel coating has an average thickness in the range of about 50 microns to about 70 microns per side, and the tape overlap is in the range of about 15% to about 70%, and the tape wrapped PAI enamel electrical conductor has a total thickness of less than about 170 microns per side.
11. The method according to any one of claims 1 to 5, wherein: Applying the enamel coating along the electrical conductor comprises: applying a polyimide PI enamel coating along the electrical conductor such that the PI enamel coating has an average thickness in a range of about 40 microns to about 45 microns per side; and Wrapping the electrical insulating tape around the enameled electrical conductor includes: wrapping the electrical insulating tape around the PI enameled electrical conductor so that the tape overlap is in the range of about 15% to about 53%, and the average insulation thickness on each side is in the range of about 75 microns to about 108 microns as defined by the PI enameled coating and the electrical insulating tape.
12. The method according to any one of claims 1 to 5, wherein: Applying the enamel coating along the electrical conductor comprises: applying a polyester-imide / polyamide-imide PEI / PAI enamel coating or a polyimide PI enamel coating along the electrical conductor such that the enamel coating has an average thickness in a range of about 50 microns to about 70 microns per side; and Wrapping the electrical insulating tape around the enameled electrical conductor includes wrapping the electrical insulating tape around the enameled electrical conductor such that the tape overlaps in a range of about 15% to about 70% and the tape-wrapped enameled electrical conductor has a total thickness of less than about 170 microns per side.
13. The method according to any one of claims 1 to 5, wherein: The electrically insulating tape includes about 10% to 25% by weight of an electrically insulating anti-corona composite filler in the polyimide; The electrically insulating tape has a thickness of less than 30 microns; Applying the enamel coating along the electrical conductor includes: applying a polyamide-imide (PAI) enamel coating along the electrical conductor such that the PAI enamel coating has an average thickness in a range of about 30 microns to about 80 microns per side; and Wrapping the electrical insulation tape around the enameled electrical conductor includes wrapping the electrical insulation tape around the PAI enameled electrical conductor such that the tape overlaps in a range of about 15% to about 70% and the tape-wrapped PAI enameled electrical conductor has a total thickness of less than about 170 microns per side.
14. An electrically insulated conductor, comprising: Conductive core; an enamel coating along said conductive core; as well as an electrically insulating tape wrapped around an enameled conductive core, the electrically insulating tape comprising a polyimide, an additional polymer adhered to the polyimide, and an electrically insulating anti-corona filler in an amount sufficient to protect against partial discharge (PD); Thereby, the enameled conductive core wrapped with the tape is resistant to PD.
15. An electrically insulated conductor as claimed in claim 14, wherein: The electrically insulating tape comprises about 17 weight percent of an electrically insulating anti-corona composite filler in the polyimide; and / or The electrically insulating corona-resistant composite filler comprises aluminum oxide.
16. The electrically insulated conductor of claim 14, wherein: the electrically insulating tape being wrapped around the enameled conductive core with a tape overlap in a range of about 15% to about 70%; said electrically insulated conductor having a total thickness of less than about 170 microns per side as defined by said conductive core, said enamel coating and said electrically insulating tape; and The enamel coating has an average thickness of less than about 90 microns per side.
17. The electrically insulated conductor of claim 14, wherein: The enamel coating along the conductive core comprises a polyamide-imide (PAI) enamel coating comprising 4,4'-methylenedianiline and trimellitic anhydride; and / or The electrical insulating tape includes a polyimide film containing pyromellitic dianhydride (PMDA) and 4,4′-diaminodiphenyl ether (ODA).
18. The electrically insulated conductor of claim 14, wherein: The enamel coating is cured; The electrical insulating tape is wrapped around the cured enameled conductive core and heat sealed to help ensure good adhesion of the electrical insulating tape to the cured enameled coating; as well as The enamel coating beneath the electrically insulating tape is configured to provide adequate electrical insulation to the conductive core when the electrically insulating tape is peeled and / or scraped away from the enameled conductive core around which the tape is wrapped.
19. The electrically insulated conductor of claim 14, wherein: The enamel coating comprises: Polyamide-imide PAI enamel coating; or Polyimide PI enamel coating; or Polyester-imide / polyamide-imide PEI / PAI enamel coating.
20. An electrically insulated conductor as claimed in any one of claims 14 to 19, wherein: The conductive core includes a copper wire, an aluminum wire or a stainless steel wire, and the copper wire, the aluminum wire or the stainless steel wire has a substantially rectangular cross-sectional shape with rounded corners; The enamel coating comprises a polyamide-imide (PAI) enamel coating along the copper, aluminum or stainless steel wire, such that the PAI enamel coating has an average thickness in a range of about 60 microns to about 65 microns per side; and The electrical insulating tape is wound around the PAI enameled copper wire, aluminum wire or stainless steel wire so that: The tape overlap is about 66% and the average insulation thickness per side as defined by the PAI enamel coating and the electrically insulating tape is about 125 microns; or The tape overlap is about 53% and the average insulation thickness per side as defined by the PAI enamel coating and the electrically insulating tape is about 123 microns; or The tape overlap was about 20%, and the average insulation thickness per side, as defined by the PAI enamel coating and the electrical insulation tape, was about 91 microns.
21. An electrically insulated conductor as claimed in any one of claims 14 to 19, wherein: The conductive core includes a copper wire, an aluminum wire or a stainless steel wire, and the copper wire, the aluminum wire or the stainless steel wire has a substantially rectangular cross-sectional shape with rounded corners; The enamel coating comprises a polyimide PI enamel coating along the copper wire, the aluminum wire or the stainless steel wire, such that the PI enamel coating has an average thickness in a range of about 40 microns to about 45 microns per side; and The electrical insulating tape is wound around the PI enameled copper wire, aluminum wire or stainless steel wire so that: The tape overlap is about 53% and the average insulation thickness per side as defined by the PI enamel coating and the electrical insulating tape is about 108 microns; or The tape overlap was about 15%, and the average insulation thickness per side, as defined by the PI enamel coating and the electrical insulation tape, was about 75 microns.
22. An electrically insulated conductor as claimed in any one of claims 14 to 19, wherein: The conductive core includes a copper wire, an aluminum wire or a stainless steel wire, and the copper wire, the aluminum wire or the stainless steel wire has a substantially rectangular cross-sectional shape with rounded corners; The enamel coating comprises a polyester-imide / polyamide-imide PEI / PAI enamel coating along the copper wire, aluminum wire or stainless steel wire, such that the PEI / PAI enamel coating has an average thickness in a range of about 60 microns to about 65 microns per side; and The electrical insulating tape is wrapped around a PEI / PAI enameled copper, aluminum or stainless steel wire such that the tape overlap is about 53% and the average insulation thickness per side as defined by the PEI / PAI enameled coating and the electrical insulating tape is about 125 microns.
23. An electrically insulated conductor as claimed in any one of claims 14 to 19, wherein The enamel coating comprises a polyamide-imide (PAI) enamel coating along the conductive core, and the electrical insulating tape is wrapped around the PAI enamel conductive core such that: said PAI enamel coating having an average thickness per side in the range of about 60 microns to about 65 microns, with a tape overlap in the range of about 20% to about 66%, and said average insulation thickness per side as defined by said PAI enamel coating and said electrically insulating tape in the range of about 91 microns to about 125 microns; or The PAI enamel coating has an average thickness in the range of about 50 microns to about 70 microns per side, and the tape overlap is in the range of about 15% to about 70%, and the tape-wrapped PAI enamel conductive core has an overall average thickness of less than about 170 microns per side.
24. An electrically insulated conductor as claimed in any one of claims 14 to 19, wherein: The enamel coating comprises a polyimide PI enamel coating along the conductive core, such that the PI enamel coating has an average thickness in a range of about 40 microns to about 45 microns per side; and The electrically insulating tape is wrapped around the PI enameled conductive core such that the tape overlap is in the range of about 15% to about 53% and the average insulation thickness per side as defined by the PI enameled coating and the electrically insulating tape is in the range of about 75 microns to about 108 microns.
25. An electrically insulated conductor as claimed in any one of claims 14 to 19, wherein: The enamel coating comprises a polyester-imide / polyamide-imide PEI / PAI enamel coating or a polyimide PI enamel coating along the conductive core, such that the enamel coating has an average thickness in a range of about 50 microns to about 70 microns per side; and The electrically insulating tape is wrapped around the enameled conductive core such that the tape overlap is in the range of about 15% to about 70%, and the tape-wrapped enameled conductive core has an overall average thickness of less than about 170 microns per side.
26. An electrically insulated conductor as claimed in any one of claims 14 to 19, wherein: The electrically insulating tape includes about 10% to 25% by weight of an electrically insulating anti-corona composite filler in the polyimide; said electrically insulating tape having a thickness of less than 30 microns, excluding said additional polymer adhered to said polyimide; The enamel coating comprises a polyamide-imide (PAI) enamel coating along the conductive core such that the PAI enamel coating has an average thickness in a range of about 30 microns to about 80 microns per side; and The electrically insulating tape is wrapped around the PAI enameled conductive core such that the tape overlap is in the range of about 15% to about 70%, and the tape-wrapped PAI enameled conductive core has an overall average thickness of less than about 170 microns per side.